(3fRgI GdfahS hGdCacGQ aj NhGU GdMjhGf hGdfHGJ hGdCMLGQs - (3YHO GdQMef Hf CHj HcQ Hf OGhO, GdMfHdj GdOeTbqj GdUGdMj,J (B856 (3g` s ((3eMeO Hf CMeO Hf Wg s)
(3ChdgG (B:s
(3hHYO (B:(3aEfi deG hbaJ Ydi cJGH eSGdc GdCHUGQ ai eeGdc GdCeUGQ s
(3BNQgG (B:s
(3eG MhJg GdOaGJQ hGdChQGb eeG GJVM ef NHGjG GdCNHGQ hGSJMSf ef LhGgQ GdBKGQ Ydi SHjd GdGNJUGQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B217 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs